2016
DOI: 10.1186/s13229-016-0074-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-twin gender on neurodevelopmental symptoms: a twin register study

Abstract: BackgroundAutism spectrum disorder (ASD) and attention-deficit/hyperactivity disorder (ADHD) are neurodevelopmental disorders thought to have both genetic and environmental causes. It has been hypothesized that exposure to elevated levels of prenatal testosterone is associated with elevated traits of ASD and ADHD. Assuming that testosterone levels from a dizygotic male twin fetus may lead to enhanced testosterone exposure of its co-twins, we aimed to test the prenatal testosterone hypothesis by comparing same-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…A recent Swedish investigation suggested that merely having a female cotwin is associated with displaying a greater degree of ADHD traits than having a male cotwin, although this study did not take account of the degree to which the index twin displayed ADHD symptoms. 13 In 1 study of a US-based twin sample, traits of ADHD were examined in the cotwins of individuals displaying a high degree of traits of ADHD. Cotwins of females displaying extreme ADHD traits displayed significantly greater ADHD-like behaviors than cotwins of males displaying extreme traits of ADHD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Swedish investigation suggested that merely having a female cotwin is associated with displaying a greater degree of ADHD traits than having a male cotwin, although this study did not take account of the degree to which the index twin displayed ADHD symptoms. 13 In 1 study of a US-based twin sample, traits of ADHD were examined in the cotwins of individuals displaying a high degree of traits of ADHD. Cotwins of females displaying extreme ADHD traits displayed significantly greater ADHD-like behaviors than cotwins of males displaying extreme traits of ADHD.…”
mentioning
confidence: 99%
“…We expected, in light of existing evidence, to find evidence of a female protective effect against ADHD behaviors. 13 , 14 …”
mentioning
confidence: 99%
“…As far as we know, no previous studies have compared the risk of epilepsy in OS and SS twins. Findings for attention deficit hyperactivity disorder (ADHD) and autism are conflicting [ 33 35 ]. Higher levels of testosterone in amniotic fluid have been associated with autism in some [ 32 ], but not all studies [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study showed the SS male twins had a higher risk of autism compared with OS male twins [ 33 ]. Other studies, however, did not support the TTT hypothesis [ 34 , 35 ]. Instead, the studies found that girls with a male co-twin had less ADHD and autistic traits than girls with a female co-twin [ 34 , 35 ] indicating the complexity of the effect of fetal hormones on brain development.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation